2021
DOI: 10.1364/jocn.419293
|View full text |Cite
|
Sign up to set email alerts
|

Power control strategies and network performance assessment for C+L+S multiband optical transport

Abstract: Spatial-division multiplexing (SDM) and band-division multiplexing (BDM) have emerged as solutions to expand the capacity of existing C-band wavelength-division multiplexing (WDM) optical systems and to deal with increasing traffic demands. An important difference between these two approaches is that BDM solutions enable data transmission over unused spectral bands of already-deployed optical fibers, whereas SDM solutions require the availability of additional fibers to repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 28 publications
0
27
1
Order By: Relevance
“…3. These NFs were obtained through experimental characterization of commercially available Erbium-doped fibre amplifiers (EDFA)s for the C-and L-bands [3] and from a benchtop Thulium-doped fibre amplifier (TDFA) for the S-band [22]. The optical amplifiers fully compensate for the loss of each channel, i.e., the gain ripple of the amplifiers perfectly compensate for the ISRS power transfer.…”
Section: Simulation Setup and Metrics A Transmission Scenariosmentioning
confidence: 99%
See 3 more Smart Citations
“…3. These NFs were obtained through experimental characterization of commercially available Erbium-doped fibre amplifiers (EDFA)s for the C-and L-bands [3] and from a benchtop Thulium-doped fibre amplifier (TDFA) for the S-band [22]. The optical amplifiers fully compensate for the loss of each channel, i.e., the gain ripple of the amplifiers perfectly compensate for the ISRS power transfer.…”
Section: Simulation Setup and Metrics A Transmission Scenariosmentioning
confidence: 99%
“…Indeed, using the launched power profile calculated by the local-optimization global-optimization (LOGO) strategy, it was shown in [2] that using 48 THz (a 10x factor in bandwidth increase) for data transmission could allow increasing the capacity of point-to-point links by about eight times, thus leading to a spectral efficiency reduction of about 20%. Even though selecting the launch power using the LOGO optimization strategy is not optimal for such wide-band systems [3], this early analysis stresses the importance of accurately estimating the capacity and cost of future MB systems to steer the development of the technology required to enable each transmission band.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MBT systems are already being deployed as C+L [4], [5], by capitalizing on the re-use of erbium-doped fiber amplifiers (EDFAs) also within the L-band. More recently, S+C+L-band systems started being subject of active research, from numerical studies [3], [6] that showed the potential of these three-band systems to triple the capacity when compared against C-band only, to experimental setups employing power optimization schemes [5], wideband semiconductor optical amplifiers (SOAs) [7], [8] and continuous bandwidth amplification and geometric shaping for record breaking data transmission [9]. As MBT systems gain commercial traction, solutions for, e.g., spectrum management and routing are required.…”
Section: Introductionmentioning
confidence: 99%